FRACTIONAL MATHEMATICAL MODELING TO THE SPREAD OF POLIO WITH THE ROLE OF VACCINATION UNDER NON-SINGULAR KERNEL - Liu, Xuan; Rahman, Mati Ur; Arfan, Muhammad; Tchier, Fairouz; Ahmad, Shabir; İnç, Mustafa; Akinyemi, Lanre (World Scientific Publ Co Pte Ltd, 2022)
This paper deals with the fractional mathematical model for the spread of polio in a community with variable size structure including the role of vaccination. The considered model has been extended with help of Atangana-Baleanu in the sense of the Caputo (ABC) fractional operator. The positivity and boundedness of solution (positively invariant region) are presented for the ABC-fractional model of polio. The fixed-point theory has been adopted to study the existing results and uniqueness of the solution for the concerned problem. We also investigate the stability result for the considered model using the Ulam-Hyers stability scheme by taking a small perturbation in the beginning. Numerical simulation is obtained with the help of the fractional Adams-Bashforth technique. Two different initial approximations for all the compartments have been tested for achieving stability to their same equilibrium points. The control simulation is also drawn at fixed infection and exposure rates at various fractional orders. The comparison at different available rates of infection and exposition is also plotted to show the decrease in the infection by decreasing these rates. Various graphical presentations are given to understand the dynamics of the model at various fractional orders.
Keywords: Fractional Model of Polio; Existence Theory; Numerical Simulations; Adams-Bashforth Method